Unproven corruption: «fraud» in the High Post of New Spain (1693-1701) - Gonzalez Martinez, Nelson Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In the late 17th century, the High Post of New Granada was accused of defrauding the Royal Treasury for a sum close to 16,000 pesos. This situation was denounced by the Count of Moctezuma, viceroy of New Spain. In this context, the High Post was made up of individuals in charge of coordinating the distribution of correspondence in some areas of Spain and the Indies. The article intends to analyze the way in which such an accusation of corruption was made and why it was not proven. In this case, this issue unleashed a scandal in Mexico and Madrid, which led to a thorough legal and accounting investigation. When the case was resolved, the person in charge of correspondence distribution in New Spain managed to keep his credibility and, in a way, redeem the good name of the postal concessions in America. This lawsuit represents the largest accusation of embezzlement ever made against the High Post within the Spanish empire.